The effect of course length on butterfly swimming performance in national and international swimmers - Wolfrum, M.; Knechtle, B.; Rüst, C. A.; Rosemann, T.; Lepers, R. (Medicina Sportiva, 2013)
Introduction: Effects of course length and recent advances on performance in butterfly swimming have not been previously investigated. Objective: The aims to this study were (i) to compare the butterfly swim performance on short (25m) versus long (50m) courses and (ii) to examine the changes in butterfly swimming speed during the 2000-2011 period for both female and male national (Switzerland) and international competitors (FINA World Championship finalists). Methods: Swimming speeds were analysed for 45,583 Swiss swimmers and for 573 FINA finalists, competing in 50m, 100m, and 200m races. Analysis of variance (ANOVA) was used to compare swimming speeds for different groups and linear regression was used to assess temporal trends. Results: Swimming speeds of swimmers at national and international level were on average 1.3±0.7% faster on short courses than on long courses for both sexes and all race distances. Sex-related differences in swimming speed were greater on short courses than on long courses for athletes at international level (P < 0.01). Sex-related differences for swimmers at national level were greater on long courses, but only for 200m races (P < 0.01). Performance of athletes at international level improved on both short and long courses (r2 = 0.58-0.88, P < 0.05), while swimmers at national level showed a consistent improvement only in long-course events (r2 = 0.37-0.74, P < 0.05). In short-course events, women at national level improved in 50m and 100m, while men at national level improved only in 100m (r 2= 0.37-0.56, P < 0.05). Conclusion: To summarize, (i) swimmers at both national and international level were ~1.3% faster on short courses compared to long courses for both sexes and all distances and (ii) performance of athletes at international level improved on both short and long courses while athletes at national level improved only on 100m for both sexes.